2005
DOI: 10.1111/j.1399-543x.2005.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction among three genomic regions creates distinct contributions to early- and late-onset type 1 diabetes mellitus

Abstract: There are two peaks in the distribution of the age of onset of type 1 diabetes mellitus (T1DM)--the first in early childhood and the second at the time of puberty. Although T1DM results from the interaction of genetic and non-genetic factors, it has not been established which factors contribute to the bimodal distribution. The genetic component of T1DM is in large part related to genes from the human leukocyte antigen (HLA) complex (IDDM1); however, loci from the variable nucleotide tandem repeat (VNTR) region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 42 publications
1
26
0
1
Order By: Relevance
“…As we know, the second and much greater peak incidence of diabetes in children is during early puberty (i.e. ages between 10 -14 years) (14). These data, therefore, were attributed to the high number of new-onset cases presenting with DKA.…”
Section: Discussionmentioning
confidence: 96%
“…As we know, the second and much greater peak incidence of diabetes in children is during early puberty (i.e. ages between 10 -14 years) (14). These data, therefore, were attributed to the high number of new-onset cases presenting with DKA.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, we needed to associate duration of T1DM to each in silico subject in a way that it was compatible with model parameters related to glucagon secretion. Using literature on T1DM incidence, [18][19][20][21][22] we generated a distribution of age at onset (which then can be easily transformed in T1DM duration by using the subject's age). Random sampling form this distribution, conditioned by age of in silico patient, allowed the generation of the duration of T1DM for each in silico subject, while respecting the incidence characteristics of the disease.…”
Section: Ra T K H T H H Scmentioning
confidence: 99%
“…Previous studies have indicated that the genetic contribution to disease could be higher among patients with an earlier disease onset. For example, the HLA class II association is stronger in early-onset T1D [32], and the same is seen for the insulin gene association [33].…”
Section: Discussionmentioning
confidence: 86%